Molecular crystals: the crystal field effect on molecular electronic structure - Yatsenko, Alexandr V. (Journal of molecular modeling, 2003)
The effect of crystal packing on the electronic structure of organic molecules was modeled by incorporation of the external electrostatic potential into the semiempirical Hamiltonian of the molecule. An empirical correction procedure was devised in order to compensate for systematic errors in the charge distribution typical of semiempirical methods. The model was applied to 79 crystal structures belonging to various syngonies and space groups. The effect of the crystal field is subject to wide variations depending on the crystal packing motif. The difference between the effect of the crystal field on the molecular electronic structure and the solvent effect modeled with COSMO is highlighted. The effect of intermolecular hydrogen bonds on the molecular electronic structure and electronic spectra was modeled with this approach, and it does not predominate over the effect of long-range electrostatic interactions. INDO/S calculations employing the crystal electrostatic potential give an insight into the origin of crystallochromy, in particular, they properly predict color difference for several groups of polymorphs.